2018
DOI: 10.1186/s12958-018-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as disruptor of the female fertility

Abstract: Both obesity and overweight are increasing worldwide and have detrimental influences on several human body functions including the reproductive health. In particular, obese women undergo perturbations of the ‘hypothalamic pituitary ovarian axis’, and frequently suffer of menstrual dysfunction leading to anovulation and infertility. Besides the hormone disorders and subfertility that are common in the polycystic ovary syndrome (PCOS), in obesity the adipocytes act as endocrine organ. The adipose tissue indeed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
331
2
46

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(389 citation statements)
references
References 77 publications
10
331
2
46
Order By: Relevance
“…Obesity is already recognized as a disease that interferes with fertility [28,29]. Obesity may affect a woman's fertility via numerous events, such as impairment of ovarian follicles development, qualitative and quantitative defects in oocyte maturation, altered fertilization, disrupted meiosis, and mitochondrial dynamics de- rangements leading to abnormal embryo preimplantation [30].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Obesity is already recognized as a disease that interferes with fertility [28,29]. Obesity may affect a woman's fertility via numerous events, such as impairment of ovarian follicles development, qualitative and quantitative defects in oocyte maturation, altered fertilization, disrupted meiosis, and mitochondrial dynamics de- rangements leading to abnormal embryo preimplantation [30].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The excess estrogens produced by the adipose tissue provides a growth signal for the endometrium that is unopposed by progesterone. Obesity also leads to higher rates of anovulation [ 21 ] with a relative risk above 2 for body mass index greater than 29 [ 22 ]; however, most obese women have normal ovulatory menstrual cycles [ 23 ]. In anovulatory women, the lack of ovulation and corpus luteum production keeps progesterone levels low.…”
Section: Estrogen-associated Risk Factors For Endometrial Cancermentioning
confidence: 99%
“…Obesity is reportedly associated with female infertility and is one of the major factors, especially in Saudi Arabia, because females are highly obese when compared with males, and the overall prevalence of obesity in the Saudi Arabia is 35.5% (Rafique and Nuzhat, 2016). However, recent lifestyle of female reproductive health is protected towards BMI, nutrients, physical activity, and stress-related jobs (Silvestris et al, 2018). Dağ and Dilbaz (2015) concluded that dropping weight would be beneficial for the reproductive effect in infertile women.…”
Section: Discussionmentioning
confidence: 99%